Data-Driven Needs Analysis for Developing Civil Servants’ Competence: The Role of HRIS and Transformational Leadership - Rajagukguk, Handyka Oktra; Zulaikha, Siti; Mayasari, Linda Ika; Kamaludin, Kamaludin (Jurnal Administrasi dan Kebijakan Publik, 2025)
The study focuses on a literature-based analysis of data-driven approaches to developing civil servants’ competencies. Using a thematic synthesis method, it reviews research findings, national policies, and institutional reports related to human resource development in the public sector. The results indicate that most civil servant training programs remain ceremonial, lack evidence-based needs assessments, and have limited impact on performance. Implementing a Human Resource Information System (HRIS) can objectively map competency gaps, support the design of relevant training programs, and improve training budget efficiency. The study highlights the need to shift from an administrative to an evidence-based training management approach as a prerequisite for building a professional, adaptive, and accountable bureaucracy. it recommends strengthening integrated personnel information systems, enhancing the analytical capacity of HR officials, and harmonizing regulations to ensure sustainability in national competency development strategies. The novelty of this study lies in its integrative conceptual framework, which combines HRIS utilization with transformational leadership as dual drivers of data-driven competency development. Practically, it provides a roadmap for optimizing competency-based training through systematic needs assessments, data integration, and leadership-driven cultural transformation to enhance efficiency, accountability, and service quality in the public sector.